Energy and quality of service aware FUZZY‐technique for order preference by similarity to ideal solution based vertical handover decision algorithm for heterogeneous wireless networks. Issue 3 (1st September 2013) - Kantubukta, Vasu; Maheshwari, Sumit; Mahapatra, Sudipta; Kumar, Cheruvu Siva
Abstract : Next generation networks will use multiple transport technologies that offer unrestricted user access to different service providers and support generalised mobility to allow consistent and ubiquitous service provisioning to users. Different networks have widely varying characteristics, which makes it difficult to maintain the requested quality of service (QoS) after executing handoff from one transport technology to another. Maintaining the QoS during handoff in heterogeneous networks needs an intelligent decision mechanism. Moreover, the developed algorithms should be energy aware as the devices involved rely on battery power. This study proposes a novel vertical handover decision mechanism namely FUZZY‐technique for order preference by similarity to ideal solution (FUZZY‐TOP), obtained by combining a fuzzy rule‐based mechanism with the technique for order preference by similarity to ideal solution approach. Simulation results based on a generalised Markov chain show that compared with existing vertical handover decision algorithms, the proposed FUZZY‐TOP decision algorithm performs better for different traffic classes.